A Study of Halal Awareness and Knowledge Among Entrepreneur Undergraduates - Mohamed Elias, Ezanee; Othman, Siti Norezam; Azbiya Yaacob, Noorulsadiqin; Saifudin, Adam Mohd (International Journal of Supply Chain Management, 2016)
Over recent decades, the halal concept has only been the concern for the Muslim, but now has spread into the global mainstream supply of industrial food and products. Some studies have shown that the lack of knowledge, awareness and understanding of the halal concept between Muslim producers of halal products may lead to the declining values of halalness. And this study intends to examine the level of halal awareness and knowledge among the Muslim students in the entrepreneurial program towards the intention to be a halal entrepreneur in the near future. The study was conducted at University Utara Malaysia as a cross-sectional study within a three month period. The data collection was gathered from the survey questionnairesspecifically from 274 students. The overall results have shown that the majority of respondents have a positive relationship between awareness, knowledge, and economy towards the intention and behaviorof producing halal products.